(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The current study was aimed at exploring the Stylistics aspects of Robert Frost’s poem “The Road Not Taken”. Frost’s selected poem has remained unexplored in terms of stylistics. The goals of the current study were to find out different poetic devices in the chosen poem and to analyse various linguistic levels in it. The data analysis for the current study used a qualitative approach. The researchers employed secondary sources for the data collecting. According to the results of the current study, the poet primarily used nouns, verbs, adjectives, and adverbs in the poem at the lexical level, the researchers looked at punctuation such full stops, commas, colons, semicolons, exclamation marks, apostrophes, dashes, question marks, and round brackets at the graph logical level. The researchers discovered prefixes, suffixes, and compounding at the morphological level, and at the phonological level, the researchers noticed many alliterations, assonance, and consonance in the poem. As far as poetic devices are concerned the researchers discovered different Metaphors, simile, symbolism, personification, and rhyme scheme.